Pendidikan dan Pelatihan Dampak Kebiasaan Buruk dalam Menjaga Kesehatan dan Estetika Gigi dan Mulut bagi Anak dan Orang tua TK Al Hidayah 2 Kelapa Gading - Arief Budiman, Johan; Sudiono, Janti; Ariwibowo, Taufiq; Juliani Hardja B, Magdalena; Nauli Komala, Olivia (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
This community service program aimed to improve knowledge and behavior regarding oral health and the impact of poor habits among children and parents at TK Al Hidayah 2 Kelapa Gading, North Jakarta. The initiative addressed oral health probems and parental anxiety about dental visits, which can negatively affect children's oral health and aesthetics. The intervention utilized a combination of interactive education, visual aids, live demonstrations, role play, parenting classes, and digital technology—including QR codes for attendance and evaluation—to enhance engagement and learning outcomes. The program involved 80 students, 11 teachers, and 40 parents, with activities conducted on May 7, 2025. Pre- and post-intervention assessments using a 15-item questionnaire revealed a significant increase in participants’ knowledge, with average correct answers rising from 8.6 to 12.6 out of 15. The use of digital tools facilitated efficient attendance tracking and evaluation, improving accuracy and participation. The results demonstrate that a comprehensive, technology-supported educational approach can effectively raise awareness and promote better oral health practices among young children and their caregivers. This model may serve as a reference for similar community-based health education initiatives in early childhood settings.